Self-esteem and family satisfaction as predictors of life satisfaction in Peruvian highland university students - Garnique-Hinostroza, Ronald; Coaquira, Odón Helar Huanca; Mamani-Benito, Oscar; Turpo-Chaparro, Josué Edison; Castillo-Blanco, Ronald; Turpo, Samuel Phala; Esteban, Renzo Felipe Carranza (Frontiers in Education, 2024)
Objective: To determine whether self-esteem and family satisfaction predict life satisfaction in university students from the Peruvian highlands.A cross-sectional, predictive design study with the participation of 848 Peruvian university students of both sexes (31.7% male and 68.3% female) whose ages ranged from 17 to 41 years old (M = 20.31 and SD = 3.66). The instruments used were Rosenberg's selfesteem scale (RSE; 2000), Olson's family satisfaction scale (FSS; 2006) and Diener's life satisfaction scale (SWLS; 1985).show that the proposed model had a fit of  2 (269) = 1709.6, p < .001, CFI = .957, RMSEA = .080, SRMR = .061, evidencing that positive self-esteem ( = .21, p < .001) and family satisfaction (β = .57, p < .001) significantly predict life satisfaction. Unlike negative self-esteem, which does not predict life satisfaction ( = -.09, p = .003).